Rice Galaxy: an open database for bioinformatic & molecular breeding analysis using 3K sequencing information - CGIAR Research Program on Rice (2019)
The Rice Galaxy is publicly available and ready to be used by researchers inside and outside CGIAR (http://galaxy.irri.org). There were 100 registered users, with 5117 job runs, and 7135 requested data sets.